PENGARUH KUALITAS PRODUK DAN PROMOSITERHADAP KEPUTUSAN PEMBELIAN : STUDI PADA DAPUR LEMBANG RESTO AND OUTBOND ACTIVITY - Cintia Sulviani, - (2009)
At this research there are three variables that is product quality, promotion and purchasing decision. Method applied ai analytic descriptive method that seeing two variables or more and that influence which then is done sampling from a population by using questionnaire as a means of data complier. Population in this research is a visitor at Dapur Lembang Resto and Outbond Activity and the sample is visitor which that moment in pursuance of purchasing decision is 100 people. Data collecting technique done that is questionnaire, interview and literature study. Purpose of this research is to know influence product quality to purchasing decision, promotion influence to purchasing decision. From data analysis and solution can be conclude in stimulant at degree of freedom 0.05 for all variable that is, quality of product and promotion influential positive to purchasing decision at Dapur Lembeng Resto and Oubond Activity. From the research result hence required quality of good product and as according to desire and costumer hope and intensively promotion so that purchasing decision of consumer can be increases, demand increases and company earning can be increase